HPTLC Screening and Alpha-Glucosidase Inhibitory Activity of Ethanolic Extract of Marang (Artocarpus odoratissimus) Core Waste Fruit - Cabantac, Aileen (JPAIR Multidisciplinary Research, 2026)
Marang (Artocarpus odoratissimus) is a native Philippine tree commonly found in Southeast Asia, used to treat various ailments. To provide a scientific basis for such a claim, this study evaluated the potential of marang, focusing on the core waste fruit, as a natural treatment for diabetes that aligns with the Sustainable Development Goals and the circular economy by reducing resource waste and minimizing environmental impact. This study utilized a quantitative, descriptive, comparative, and experimental design to analyze data on the phytochemical constituents and alpha-glucosidase inhibitory activity. For the evaluation of glucosidase inhibition activity, in vitro methods, and statistical such as mean, standard deviation, One-Way ANOVA, Regression and Post Hoc were applied. HPTLC screening revealed the presence of primary metabolites, including proteins, suggesting possible medicinal properties. Results showed a statistically significant difference (p<0.05) at the 95% confidence level between acarbose and marang core waste fruit extract. The IC50 of the extract of marang core waste fruit shows (203±4.15ug/mL), demonstrating a significant difference to acarbose (125±0.48 ug/mL). Overall, the findings showed that the marang core waste fruit is a potential alternative herbal medicine as an alpha-glucosidase inhibitor for diabetes.